KEEPING IT SECRET: MOTHERS’ CONCERNS IN DEALING WITH THE UNDISCLOSED PATERNITY OF THEIR CHILDREN - Manyatshe, Livhuhani; Nduna, Mzikazi (Gender Questions, 2016)
<span style="font-family: 'AvantGarde Bk BT','sans-serif'; font-size: 8pt; mso-ansi-language: EN-ZA; mso-fareast-language: EN-ZA; mso-bidi-font-family: 'Times New Roman'; mso-fareast-font-family: 'Times New Roman'; mso-bidi-language: AR-SA;">Children who grow up not knowing their biological fathers blame their mothers for being secretive and alienating them from their fathers. Research on undisclosed fathers has not shed light on why mothers would not inform the children of their fathers’ identities. This study, set in South Africa, explored maternal non-disclosure with the specific aim of creating an understanding of women’s motivations for withholding information or not introducing a child to his/her father. The research employed an exploratory qualitative approach and used an interpretive approach to garner from narratives of mothers and guardians their experiences of living with non-disclosure. Eight, one-on-one in-depth interviews were conducted with participants aged 33 to 60. Through thematic analysis, women’s first-hand accounts could be described and the essence of the phenomenon for all the participants collated. The findings suggest a supposition that there were broader challenges for mothers on how to go about the disclosure in terms of what to say to the child, and at what age it would be appropriate to start discussing the father. The fleeting discussions that did at times occur around the father indicate that disclosure is not a static event, but rather a fluid and an ongoing process. Based on the findings of our research this article provides insight into supportive strategies that may be devised to aid mothers who wish to disclose